(3GdJfXje GdbGfhfi dUfOhb GdESJKeGQ GdYbGQi (B/ s - (3CSGeI YOfGf GdMdjHis; (3CMeO aGQhb hTGMi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3JCJi CgejI GdHMK GdJfXje GdbGfhfi dUfOhb GdESJKeGQ GdYbGQi ef MjK Cfg jHjf GdOhQ GdgGe dCMO GdCOhGJ GdESJKeGQjI h gh UfOhb GdESJKeGQ GdYbGQi(B: (3ef NdGd JMhjd Gdbje GdYbGQjI Gdi eGdjI Ydi Tcd hKGFb ESJKeGQjI(B: (3jJe JOGhdgG ai HhQUI GdChQGb GdeGdjI, h JJeKd CgejI GdHMK CjVG ajeG jJYdb HHOA ONhd gPG GdfhY ef GdUfGOjb ai GdShb GdeGdi GdeUQi h JPdjd GdYbHGJ h JNaja hWCI GdCSYGQ GdJi hUdJgG GdYbGQGJ ai GdShb GdeUQi; h EjVGM Cge GdeTcdGJ h GdMdhd GdJi jLH Cf JJNP dJCNP gPg GdUfGOjb OhQgG ai GdMdbI GdEbJUGOjI(B. (3h Je JbSje GdOQGSI Gdi HGHjf jSHbge aUd JegjOi(B: (3MjK JfGhd GdaUd GdJegjOi HjGf eG gjI UfGOjb GdESJKeGQ(B: (3CeG Yf GdHGH GdChd(B: (3abO Med YfhGf Gdgjcd GdJfXjei dUfOhb GdESJKeGQ GdYbGQi(B: (3HjfeG Med GdHGH GdKGfi YfhGf GdbhGYO GdbGfhfjI GdfGXeI dCfTWI UfOhb GdESJKeGQ GdYbGQi(B. (3h bO GfJgJ GdQSGdI HeLehYI ef GdfJGFL GdJhUjGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2019s
(3HHdjhLQGajG(B: (3UaMGJ (B306-321s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3UfGOjb GdESJKeGQs; (3UfOhb GdESJKeGQ GdYbGQis; (3eOjQ GdESJKeGQs; (3GdQbGHI Ydi UfGOjb GdGSJKeGQs; (3GdUfOhb GdYbGQjs; (3GdTNUjI GdeYfhjI dUfGOjb GdGSJKeGQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs